2016
DOI: 10.1371/journal.pone.0143729
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Burden of Bloodstream Infections Caused by Extended-Spectrum Beta-Lactamase Producing Enterobacteriaceae in a Pediatric Hospital in Senegal

Abstract: ContextSevere bacterial infections are not considered as a leading cause of death in young children in sub-Saharan Africa. The worldwide emergence of extended-spectrum beta-lactamase producing Enterobacteriaceae (ESBL-E) could change the paradigm, especially in neonates who are at high risk of developing healthcare-associated infections.ObjectiveTo evaluate the epidemiology and the burden of ESBL-E bloodstream infections (BSI).MethodsA case-case-control study was conducted in patients admitted in a pediatric h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 43 publications
3
47
0
3
Order By: Relevance
“…ESBL-E occur worldwide in both community and hospital settings (Paterson and Bonomo, 2005;Pitout et al, 2005;Sonda et al, 2016;Storberg, 2014;Luvsansharav et al, 2011), and the reported incidence of infections in paediatric and neonatal populations is increasing (Paterson and Bonomo, 2005;Sonda et al, 2016;Storberg, 2014;Flokas et al, 2017;Peirano and Pitout, 2010;Tansarli et al, 2014;Dramowski et al, 2015;Logan et al, 2014). Clinical infections with ESBL-E are associated with increased morbidity (including prolonged hospital stay), increased healthcare costs, and higher mortality rates compared to infections with non- ESBL-E (Blomberg et al, 2005;Zaoutis et al, 2005;Kim et al, 2002;Ndir et al, 2016). Among neonates, children, and pregnant/ post-partum women, ESBL-E are frequently implicated in urinary tract infections (UTI) (Pitout et al, 2005;Peirano and Pitout, 2010) and bloodstream infections (BSI) (Luvsansharav et al, 2011;Flokas et al, 2017;Dramowski et al, 2015;Zaoutis et al, 2005;Loh and Sivalingam., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ESBL-E occur worldwide in both community and hospital settings (Paterson and Bonomo, 2005;Pitout et al, 2005;Sonda et al, 2016;Storberg, 2014;Luvsansharav et al, 2011), and the reported incidence of infections in paediatric and neonatal populations is increasing (Paterson and Bonomo, 2005;Sonda et al, 2016;Storberg, 2014;Flokas et al, 2017;Peirano and Pitout, 2010;Tansarli et al, 2014;Dramowski et al, 2015;Logan et al, 2014). Clinical infections with ESBL-E are associated with increased morbidity (including prolonged hospital stay), increased healthcare costs, and higher mortality rates compared to infections with non- ESBL-E (Blomberg et al, 2005;Zaoutis et al, 2005;Kim et al, 2002;Ndir et al, 2016). Among neonates, children, and pregnant/ post-partum women, ESBL-E are frequently implicated in urinary tract infections (UTI) (Pitout et al, 2005;Peirano and Pitout, 2010) and bloodstream infections (BSI) (Luvsansharav et al, 2011;Flokas et al, 2017;Dramowski et al, 2015;Zaoutis et al, 2005;Loh and Sivalingam., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…10 , no encontraron incremento en la probabilidad de morir en función de las BLEE. Ndir A. y cols., (Senegal) 3 , describieron que la mayoría de pacientes con infección por EP-BLEE reciben un esquema antimicrobiano empírico inadecuado (94,2 vs. 5,7%, p < 0,0001), lo que incrementa la tasa de mortalidad (OR 2,9, IC 95% 1,8-7,3).…”
Section: Discussionunclassified
“…as β-lactamasas de espectro extendido (BLEE), enzimas bacterianas que tienen la capacidad de inactivar penicilinas, monobactámicos y cefalosporinas, se trasmiten a través de plásmidos entre bacterias de la misma o de diferente especie. 1,2 En países en vías de desarrollo, donde la principal etiología de sepsis neonatal son enterobacterias, este mecanismo de resistencia cobra importancia por las implicaciones desfavorables sobre la morbilidad y/o mortalidad neonatal 3,4 .…”
unclassified
“…[11] The widespread and uncontrolled use of cephalosporins has contributed to the increased prevalence of ESBL-producing organisms, which may lead to increased BSI mortality, longer hospital stays and increased healthcare costs. [12][13][14] The changing spectrum of pathogens, AMR patterns and clinical impact necessitates ongoing auditing, monitoring and publication of data on local pathogen profiles and antibiotic sensitivity patterns to inform clinical management and infection prevention efforts. [6,13,14] For neonates and children admitted to SA district hospitals, research on the epidemiology and AMR patterns of CA-and HA-BSI will inform development of appropriate empirical antibiotic recommendations.…”
Section: Researchmentioning
confidence: 99%
“…[12][13][14] The changing spectrum of pathogens, AMR patterns and clinical impact necessitates ongoing auditing, monitoring and publication of data on local pathogen profiles and antibiotic sensitivity patterns to inform clinical management and infection prevention efforts. [6,13,14] For neonates and children admitted to SA district hospitals, research on the epidemiology and AMR patterns of CA-and HA-BSI will inform development of appropriate empirical antibiotic recommendations. Furthermore, there are very limited data on paediatric clinicians' prescribing practices to inform antimicrobial stewardship programmes at district hospitals.…”
Section: Researchmentioning
confidence: 99%